Germinative characteristics of Colicodendron scabridum (Kunth) Seem. : Promisory resource for reforestation and food in Peru - Mostacero León, José (2018)
Nowadays the export market is headed by commercial species such as: "grape", "mango", "pineapple", "avocado", "blueberry", among others; most of them, species introduced and adapted to our climates; which brings high production costs, leaving aside our native fruit trees, many of which grow as weeds, adapted to the environment, and have organoleptic and nutritional characteristics over commercial ones; being just waiting for its production on a large scale, so it is urgent to start with basic works such as the germinative characteristics and from there to encourage further research.For this reason, it was decided to determine the Germination Characteristics of Colicodendron scabridum (Kunth) Seem. as a promising resource for the Peruvian population's diet.For this purpose, collections of the species to be studied were carried out, to later identify it in the Herbarium Truxillensis (HUT) and finally to transfer them to the laboratory, where the germinative characteristics were determined. It is concluded that the germination characteristics of Germination Percentage, Germination Rate, Germination Uniformity, germination value and Emergency Percentage for Colicodendron scabridum (Kunth) Seem are: 94%, 6.87 days, 6.67 days, 93.33% and 116.17 respectively